(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
All things or matter both genomic-things and nongenomic-things are composed of the elements found on periodic table. In other words, nuclear energy reactions of Physics involving atoms or elements such as uranium, chemical reactions of Chemistry, and enzymatic reactions of Genomology are subsets of the elements found on the Modern Periodic Table. An atom is the fundamental particle of an element, while an element is a pure substance made of only one type of atom. The key objective of this study is to impart the etymological accuracy of the term Genomology and the reasons for the better development of Chemistry and Physics than Biology. The contents of Figures and Tables herebelow are designed to serve as evidential components of Methods & Results in the targetful strategy of this study and that is why it is entitled Methodology & Results hereabove. Genomology is the first branch of natural sciences that has converged the teaching of Bible & the set of the three branches of Natural Sciences into a Unified Package of Universal Truth , because the very characteristic features of both Bible and Natural Sciences are absolutely the search for Truth. That is the reason for why the persons who are ordered by court to give statements of witness are obliged to touch Holy Bible or Holy Kuran with their hands during witnessing.